Towards an integrated model of silver entrepreneurship success: Exploring the entrepreneurial factors and the ecosystem for productive aging. - Ahmad, Noor Hazlina (Universiti Sains Malaysia, 2014)
This research aims at proposing a framework for productive aging among employees aged 45-plus or early retirees who have switched into entrepreneurship career. It is acknowledged that this group possesses relevant industry experience, knowledge and well-established networks built up over their working careers which will enable them to effectively manage their ventures. However, there is little research on what drives these silver entrepreneurs to venture into entrepreneurship and the factors that made them successful. The findings revealed that silver entrepreneurs' motivation to start a business are related to career progression, personal wealth, family security, opportunity recognition and the pursuit of a more balanced life. It was also found that factors related to entrepreneurial competencies, entrepreneurial attitude, financial availability and business environment affect the business performance of the silver entrepreneurs. Surprisingly however, networking appears to be non-significant. This effort is deemed crucial since fostering silver offers a productive aging among mature people given the heighten percentage of aged population in the country. Encouraging silver entrepreneurship could assist in transforming the socio-economic well-being of the society at large, which is in line with Malaysia's national agenda to transform the society to become a high income society via New Economic Model.